IMPLEMENTASI MANAJEMEN OPERASIONAL LIMBAH MEDIS PADAT DI RUMAH SAKIT PT. CHEVRON PACIFIK INDONESIA - Adrian Adrian; Thamrin Thamrin; Jimmi Copriady (Jurnal Ilmu Lingkungan, 2016)
The research present describe the implementation Health of Minister decisions Number: 1204/Menkes/Sk/X/2004 about environmental health characteristic in rules Hospital of head district in Health and Medical Service Chevron Pacific Indonesia District Duri. Waste management likes liquid or solid form can be a disaster for paramedics and human. The research use the methode are qualitative methodes that analyze problem research by describe the subject and object conditions based on real fact. This research use location in Health and Medical Service Chevron Pacific Indonesia District Duri and researcher collect data from literature study, government regulation, website and deep interview with staff in Health and Medical Service Chevron Pacific Indonesia District Duri, Business Partner Health and Medical Service Chevron Pacific Indonesia District Duri. The conclusion of this research are the implementation of medic waste management in Health and Medical Service Chevron Pacific Indonesia District Duri are have done by cooperation with the Hasakona Binacipta as a Business Partner with the steps are containered waste, collected waste, carry away waste, managed waste by incinerator machine.quality had a strong connection, water quality parameters were measured at 64.8% affected total bacteria and 35.2% were influenced by other factors.